Associations between angiotensinogen M235T polymorphisms and the risk of diabetic nephropathy: A meta-analysis. (August 2018) - Zhou, Bo; Wen, Min; Mi, Ling; Hu, Cu-Jiao; Zhang, Yi; Wang, Jian-Tar; Tang, Lei
Abstract: Aims: The aim of the present study was to clarify the potential relationship of angiotensinogen (AGT) M235T polymorphism and diabetic nephropathy (DN) risk. Methods: Comprehensive electronic search in Pubmed, Web of Science, EBSCO, Embase, the Cochrane Library and China National Knowledge Infrastructure (CNKI) to find original articles about the association between AGT M235T polymorphism and DN risk published before 27 September 2017. Literature quality assessment was performed with the Newcastle-Ottawa Scale. Heterogeneity across studies was assessed using I 2 statistics. Random-effects model or Fixed-effects model was used to estimate the odds ratios (ORs) with 95% confidence intervals (CIs). Sensitivity analyses to assess the influence of individual studies on the pooled estimate. Publication bias was investigated using funnel plots and Egger's regression test. Analyses were performed by using Stata 15.0. Results: Overall, 20 eligible studies involving a total of 3822 cases and 3911 controls were included in our meta-analysis. The results showed that AGT M235T polymorphism significantly increased DN risk in recessive model (T/T versus M/T + M/M: OR = 1.35, 95%CI (1.07–1.69), I 2 = 63.8%, Z = 2.56, P = 0.010), homozygote model (T/T versus M/M: OR = 1.46, 95%CI (1.11–1.92), I 2 = 62.4%, Z = 2.69, P = 0.007) and allele model (T versus M: OR = 1.17, 95%CI (1.01–1.35), I 2 = 72.5%, Z = 2.14, P = 0.032); Subgroup analysis by ethnicity showed that AGT M235T polymorphism significantly increased DN risk in recessive model (T/T versus M/T + M/M: OR = 1.39, 95%CI (1.06–1.81), I 2 = 66.6%, Z = 2.42, P = 0.016), homozygote model (T/T versus M/M: OR = 1.47, 95%CI (1.08–2.01), I 2 = 67.7%, Z = 2.47, P = 0.013) and allele model (T versus M: OR = 1.18, 95%CI (1.02–1.37), I 2 = 69.4%, Z = 2.26, P = 0.024) in Caucasian DM population; Subgroup analysis by clinical subtype of DM also showed that AGT M235T polymorphism significantly increased DN risk in recessive model (T/T versus M/T + M/M: OR = 1.28, 95%CI (1.05–1.57), I 2 = 21.3%, Z = 2.40, P = 0.016), homozygote model (T/T versus M/M: OR = 1.41, 95%CI (1.04–1.92), I 2 = 30.2%, Z = 2.23, P = 0.026) and allele model (T versus M: OR = 1.14, 95%CI (1.03–1.28), I 2 = 35.5%, Z = 2.44, P = 0.015) in type 1 diabetes patients. Conclusion: Our study showed that AGT M235T homozygous mutation significantly increase DN risk in Caucasian DM population and type 1 diabetes patients.